Olympic women's rugby 7s: The new rugby athlete - McCallum, K. (7th World Congress on Science and Football (WCSF), 2011, 2011)
The recent inclusion of Rugby 7s in the 2016 Olympics has changed countries support of women`s rugby 7s and helped to encourage its growth to 200,000 participants in 80 countries worldwide. Women`s rugby 7s is a physically demanding sport requiring the incorporation of power, speed, strength and fitness. Significantly, many of these same elements are also found in sports such as touch rugby, basketball, volleyball and track and field, and rugby unions are looking to these other sports in their attempts to recruit the best athletes for women`s rugby 7s. Drawing on Koivula`s (2001) assertion that sports are categorized as gender neutral, feminine and masculine, I will explore how women`s rugby 7s has the potential to change from a previously masculine identity to a gender neutral one, and how (if) this will alter current perceptions and stereotypes about women`s rugby 7s and its athletes. Methods Recent statistics gathered from the Women`s World Cup 2010, 7s World Cup 2009 and 7s international tournaments will be examined to illustrate the transfer of select athletes from a range of `gender neutral` sports into women`s 7s and to explore how they compare to other experienced rugby players. I will also draw on previous literature examining stereotypes and perceptions about rugby as well as my experience coaching, playing and interviewing 7s athletes. Results Statistics from recent international 7s tournaments show that many of the standout athletes have previously excelled in other `gender neutral` sports. For instance, in the Women`s World Cup 2010, 60% of the top try scorers had played 3 years or less for their country, yet 80% of them excelled internationally in other `gender neutral` sports with one athlete winning a gold medal in Bobsled at the 2010 Olympic Winter Games. Similarly, at the Rugby World Cup 7s 2009, 50% of tries were scored by athletes with less than 3 years rugby union international experience. Anecdotal evidence (i.e. interviews, personal experience) suggests that with the inclusion of rugby 7s in the Olympic Games, elite athletes from a range of `gender neutral` sports will be encouraged to play rugby 7s. Conclusion With Women`s rugby 7s becoming an established Olympic sport, players previously engaging at elite levels in `gender neutral` sports may perceive rugby 7s to be the pinnacle of their career. What remains to be seen is how (or if) perceptions and stereotypes around women`s rugby 7s may shift and change with the recent developments and the rise in media attention that will likely accompany them.